Laparoscopic Nissen Fundoplication A Minimal Access Alternative - Troch, Priscilla (Operating Room Nurses Association of Canada Journal, 1994)
The preferred treatment of gastroesophageal reflux has traditionally been Nissen fundoplication. This involves an extensive abdominal or thoracic incision and subsequently results in patient discomfort, an extended recov- ery period, and increased overall costs. In the advent of laparoscopic advances surgical correction of symptoms of gastroesophageal reﬂux are now being offered through minimal access surgery. Increased patient satisfaction, decreased costs, and a quicker return to activities of daily living, suggest why laparoscopic Nissen fundoplication, (LNF) is fast becoming the preferred alternative to correction of gastroesophageal reﬂux disease. This article will review gastroesophageal reﬂux and describe one surgical method oflaparoscopic correction. The role of the perioperative nurse and implementation of the nursing process regarding this surgical procedure will be highlighted.